Pola Dasar Penggunaan Brand Dari masa ke Masa - Angga Hendrawan (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2014)
The problem in this study is the number of practitioners who consider branding as a job in the visual field. The purpose of this study was to identify the structure and function of the brand from time to time, so it can look a basic pattern that always exists in every development. This study uses literature by studying scientific sources. Developments brandditemukan usage patterns starting in 2250SM to the current pattern of development in the conventional use of a brand starts to become a strategic device, which is able to influence the development activities bisnis.Seiring with the times, the brand experienced a transformation function that directs a business to remain competitive to cope with change times.